Recursion Example One
Defining Rule

t1 = 20

tn = tn-1 - 10


Generating the Sequence

Knowing that the first terms is twenty (t1 = 20), calculate the value of the second term (t2)

Since we need to calculate t2, substitute n = 2 into the second part of the recursive rule (tn = tn-1 - 10)


      t(2) = t(2)-1 - 10

      t2 = t1 - 10                  (But it is known that t1 = 20)

      t2 = 20 - 10

      t2 = 10


Repeat this process to find t3.

Knowing that the first two terms are twenty and ten (t1 = 20 and t2 = 10), calculate the value of the third term (t3)

Since we need to calculate t3, substitute n = 3 into the second part of the recursive rule (tn = tn-1 - 10)


      t(3) = t(3)-1 - 10

      t3 = t2 - 10                  (But it was calculated that t2 = 10)

      t3 = 10 - 10

      t3 = 0


Repeat this process to find t4.

Knowing that the first three terms are twenty, ten and zero (t1 = 20, t2 = 10 and t3 = 0), calculate the value of the fourth term (t4)

Since we need to calculate t4, substitute n = 4 into the second part of the recursive rule (tn = tn-1 - 10)


      t(4) = t(4)-1 - 10

      t4 = t3 - 10                  (But it was calculated that t3 = 0)

      t4 = 0 - 10

      t4 = -10


Repeat this process to find as many terms as required.


Sequence: 20, 10, 0, -10, -20, -30, -40, . . .

Sequence: Starting with twenty, subtract ten from each term of the sequence to determine the next term of the sequence.